Recent Advances in Magnesium Carbenoid Chemistry - Kimura, Tsutomu (Synthesis, 2017)
Magnesium carbenoids are a class of organomagnesium species possessing a halo group at the α-position. The reactions of magnesium carbenoids can be classified into the following three categories: nucleophilic reactions resembling Grignard reagents, electrophilic reactions resembling organic halides, and rearrangements resembling carbenes. This short review summarizes recent studies on magnesium carbenoids reported between 2010 and 2016, and milestone studies reported before 2010 according to the classification of the reactions into the aforementioned three categories.1 Introduction2 Structures of Magnesium Carbenoids3 Reactions of Magnesium Carbenoids as Nucleophiles3.1 Nucleophilic Reactions of Magnesium Carbenoids3.2 Nucleophilic Reactions of Magnesium Alkylidene Carbenoids3.3 Nucleophilic Reactions of Cyclopropylmagnesium Carbenoids4 Electrophilic Reactions of Magnesium Carbenoids4.1 Reactions with Nucleophiles Followed by Electrophiles4.2 Reactions with Nucleophiles Possessing Electrophilic Functional Groups4.3 Nucleophilic Substitution Followed by β-Elimination5 Rearrangements of Magnesium Carbenoids5.1 1,2-Shifts of Magnesium Carbenoids5.2 1,3-C–H Insertions of Magnesium Carbenoids5.3 1,5-C–H Insertions of Magnesium Carbenoids5.4 [2+1] Cycloaddition of a Magnesium Carbenoid6 Conclusion and Outlook
Keywords: magnesium; carbenoids; carbenes; Grignard reaction; organometallic reagents; rearrangement; sulfoxides